Rancangan Desain Tampilan Website Dinas Perpustakaan Dan Arsip Kota Balikpapan Menggunakan Kansei Engineering - Rizalmi, Sigit Rahmat; Maharani, Yuniar; Anggraini, Novita Lizza (Universitas Al Azhar Indonesia, 2025)
The City Library and Archives Office utilizes its website to deliver information and services. However, its development has not yet considered user comfort and an adequate User Interface (UI) design, which reduces user satisfaction. This study aims to identify the elements that influence interface design and determine the reference specimen for UI design recommendations. The research employs the Kansei Engineering (KE) approach to connect user emotions with design elements. Data were collected through a questionnaire using 28 Kansei words to analyze five website specimens, involving 50 respondents. The analysis was conducted using Principal Component Analysis (PCA), Factor Analysis, and Partial Least Squares (PLS). The results indicate that the Kansei word